Rome and Canterbury the Elusive Search for Unity. - Reath, Mary. (Lanham : Rowman & Littlefield Publishers, 2007)
Rome and Canterbury tells the story of the determined but little known work being done to end the nearly five hundred year old divisions between the Roman Catholic and the Anglican/Episcopal Churches. The break was never intended, has never been fully accepted and is experienced, by many, as a painful and open wound. It is a personal account that begins the story by reviewing the relevant history and theology, looks at where we are today, and concludes with some reflections on faith and belief in the U.S.
Appendix VII: Population by Continent (400 BC to 1600 AD)Appendix VIII: Resources; Bibliography; Acknowledgments; Index.
Description based on print version record.
Keywords: Episcopal Church -- Relations -- Catholic Church; Catholic Church -- Relations -- Episcopal Church; Christian union -- United States; RELIGION / Christianity / Denominations; Electronic books